Proses Pembentukan Konsep Diri Remaja Akhir Indigo - Muhammad Razan Abdurahman; Anisa Diniati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Self-concept plays a role in shaping oneself, self-attitude, valuing oneself and others and the surrounding environment. Most people who knows indigo as a negative ability in an indigo person. The formulation of the problem of this research is how the process of forming the self-concept of indigo late-adolescents with the aim to find out how the process of an indigo adolescent faces the turmoil that comes from within themselves or others or the surrounding environment to form a concept within themselves. This study uses a qualitative approach using interviews, observation, and documentation as data collecting. The results of this study indicate that the process of self-concept formation of indigo adolescents in the informants has begun since childhood until the age of adolescence at this time. The process of forming the self-concept was obtained from interaction and communication by the informants. Through this interaction and communication, the formation of self-concept experiences various obstacles until finally the informants can accept themselves and feel comfortable with their indigo abilities.